Dental unit water: bacterial decontamination of old and new dental units by flushing water - E Watanabe (Journal compilation 2008 Blackwell Munksgaard, 2008)
To evaluate by means of PetrifilmTM system (3M, St Paul, MN, USA) the level of bacterial contamination in water from old and new dental units (air–water syringes and high-speed turbines) before and after flushing water through waterlines.